2009
DOI: 10.1177/0898264309347821
|View full text |Cite
|
Sign up to set email alerts
|

The Health Impact of a Hearing Disability on Older People in Australia

Abstract: Data support emerging literature suggesting a causal relationship between hearing disability and quality of life. Prospective studies to further examine this relationship are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 16 publications
6
69
1
3
Order By: Relevance
“…A study that evaluated hearing loss among older Australians found 71% of individuals with limited communication 34 . Tanaka, Araujo and Assencio-Ferreira 35 on investigating the consequences of hearing loss in the elderly communication observed that auditory deficits did not compromise significantly; being neurological problems more responsible for communication disorders in that group.…”
Section: Discussionmentioning
confidence: 99%
“…A study that evaluated hearing loss among older Australians found 71% of individuals with limited communication 34 . Tanaka, Araujo and Assencio-Ferreira 35 on investigating the consequences of hearing loss in the elderly communication observed that auditory deficits did not compromise significantly; being neurological problems more responsible for communication disorders in that group.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing difficulty ranked third behind respiratory disease and arthritis in negative impact on the physical health component score and second to digestive disorders on the mental health component score. Data from the 2003 Australian Survey of Disability, Aging and Carers also demonstrated that among adults aged 55 years and older, reporting a hearing disability was associated with lower age-specific healthrelated quality of life in both physical and mental health scales on the SF-12 quality-of-life survey (23).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Kvam, Loeb, and Tambs (2007) further found that negative childhood experiences (e.g., parental abuse, bullying, and sexual abuse) increased the probability of mental health problems in deaf adults. Hearing spouses of people with acquired deafness have additionally reported comparatively poorer psychological, physical, and social wellbeing when measured with population norms (Fellinger et al, 2005;Hogan et al, 2001;Hogan, O'Loughlin, Davis, A., & Kendig, 2009b).…”
Section: Mental Health and Professional And Social Participation In mentioning
confidence: 99%
“…Larger studies by Hintermair (2008) and Hogan et al (2009b) suggested that many themes in the smaller studies are prevalent across the broader population of deaf people. When interacting with hearing peers, deaf individuals are often required to make sense ofand to concurrently act upon -the social situation with less-than-ideal hearing.…”
Section: Mental Health and Professional And Social Participation In mentioning
confidence: 99%
See 1 more Smart Citation